2014
DOI: 10.1136/bjsports-2014-093494.224
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Impact on Performance of Athletes Participating in the London 2012 Olympic Games

Abstract: BackgroundOral health is important both for wellbeing and successful elite sporting performance. Reports from Olympic Games have found significant treatment needs; however, few studies have examined oral health directly.ObjectiveThe aim of this study was to evaluate oral health, the determinants of oral health and the effect of oral health on wellbeing, training and performance of athletes participating in the London 2012 Games.DesignCross-sectional study.SettingDental clinic within the London 2012 Polyclinic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
0
13
0
5
Order By: Relevance
“…Approximately 30% of all players had periodontitis which was higher from previous studies (15 % of athlete participating in the London 2012 Olympic Games). 4 Poor oral hygiene is risk factor of all oral disease. 13 The oral hygiene instruction should be included in for health program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 30% of all players had periodontitis which was higher from previous studies (15 % of athlete participating in the London 2012 Olympic Games). 4 Poor oral hygiene is risk factor of all oral disease. 13 The oral hygiene instruction should be included in for health program.…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous study shows that the significant of oral health and impact on performance of athletes participating in the London 2012 Olympic Game, whereas this study failed to find the relationship of oral health status and quality of life might be from the small number of samples. 4 Better oral health will improve quality of life and performance of soccer player.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also have a negative impact on the athletes' training, performance, and general well-being. [38][39][40] The present systematic review with meta-analysis showed a wide range and a prevalence of dental caries, affecting 36.5% (95% CI = 30.6 to 42.7) of the athletes with intellectual disabilities. Similar to our results the Global Burden of Disease Study (2010) 1 observed that the global prevalence of untreated caries in permanent teeth in the general population was 35.29% for all ages combined.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, the long-term presence of microorganisms is a major cause of oral diseases such as gingivitis and dental caries. The presence of an oral infection during sports may have a negative impact on athletes [9].…”
Section: Introductionmentioning
confidence: 99%